Evaluation of Antibiotic Prescribing Patterns in Paediatric Dental Patients: Cross - Sectional Epidemiological Study - Yigit Tugba; Ezberci Sibel; Topal Burcu Gucyetmez (Balkan Stomatological Society, 2021)
Background/Aim: The purpose of this study was to investigate the antibiotic prescribing patterns for the treatment of paediatric oral infection, dental trauma and prophylaxis among dentists in Turkey.